EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN BAWANG MERAH (Allium ascalonicum L.) DI KECAMATAN MUARA KABUPATEN TAPANULI UTARA - Nurhalimah Rajagukguk*, Zulkifli Nasutio Rajagukguk; Zulkifli Zulkifli; Razali Razali (Universitas Sumatera Utara, 2014)
The objective of this research is to evaluate the land suitability onion (Allium ascalonicum L.) inMuara Subdistrict of North Tapanuli District. The methode of this research is the survay method.From the results of the overlay from the map of soil types, map of topography, and map of heightplace, retrieved 3 (three) units of land use map. SPL 1 has a land area of 741 hectares, SPL 2 has aland area of 13 hectares, and SPL 3 has a land area of 609 hectares.With the Matching method, thenretrieved the land suitability class actual and potensial class for onion (Allium ascalonicum L.) oneach of the SPL. At SPL 1 and SPL 2 are actual land suitability class S3 (nr) while the potentialland suitability class is S2 (tc) and at SPL 3 is actual land suitability class S3 (nr,eh) while thepotential land suitability class is S2 (tc,eh).Key words : land suitability (onion)